2010
DOI: 10.1111/j.1470-6431.2009.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding consumer receptivity towards foods and non‐prescription pills containing phytosterols as a means to offset the risk of cardiovascular disease: an application of protection motivation theory

Abstract: Consumer purchase intention with respect to foods and non‐prescription pills containing phytosterols was investigated through a mall intercept survey (n = 446) in Ontario, Canada. The study took as its starting point the Protection Motivation Theory (PMT), a social cognition model rooted in research on fear appeal in determining health‐protective behaviour. Structural equation modelling was used to explore whether an adaptation of PMT explains intention to purchase products containing phytosterols as a means t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 96 publications
(177 reference statements)
1
19
2
Order By: Relevance
“…Self-efficacy was the most effective predictor of intention (β = 0.65), followed by perceived response efficacy (β = 0.28) and perceived rewards (β = - 0.12). Park et al ( 31 ) explored functional food consumption behavior and reported that self-efficacy and perceived response efficacy were significant predictors of intention, which chimes in with our results The authors also reported that severity and vulnerability were also not significant predictors of intention, which is concordant with our results but discordant with the results of some other investigations ( 32 - 34 ). The non-significant relation between the other constructs and intention can be explained by the notion that in Iranian society women value rewards because they are extremely influenced by subjective norms (family or friends) and that the mean age among our female subjects was 38.45 years.…”
Section: Discussionsupporting
confidence: 90%
“…Self-efficacy was the most effective predictor of intention (β = 0.65), followed by perceived response efficacy (β = 0.28) and perceived rewards (β = - 0.12). Park et al ( 31 ) explored functional food consumption behavior and reported that self-efficacy and perceived response efficacy were significant predictors of intention, which chimes in with our results The authors also reported that severity and vulnerability were also not significant predictors of intention, which is concordant with our results but discordant with the results of some other investigations ( 32 - 34 ). The non-significant relation between the other constructs and intention can be explained by the notion that in Iranian society women value rewards because they are extremely influenced by subjective norms (family or friends) and that the mean age among our female subjects was 38.45 years.…”
Section: Discussionsupporting
confidence: 90%
“…All constructs had a significant relationship with intention, secondly; using adjusting model, three constructs were ranked based on strongest to the weakest including self-efficacy (β = 0.65), perceived response efficacy (β = 0.28) and perceived reward (β = -0.12). The study by Park, investigating functional food consumption behavior, showed that self-efficacy and perceived response efficacy were significant predictors of intention (46) that was similar to the current study findings; in addition, severity and vulnerability were not significant predictors of intention; confirming the current study results, while differing from those of other studies (47)(48)(49). The non-significant relationship of other PMT constructs with intention may be caused by the variety of subjects.…”
Section: Predicting Intention Based On Pmt Constructscontrasting
confidence: 51%
“…Measuring perceived negative health concern toward GM food had a negative effect on consumers’ willingness to purchase GM food (Amin et al., ), as was perceived severity of eating irradiated meat (Crowley, Marquette, Reddy, & Fleming, ). Nevertheless, for the case of severity of a health threat (for example, frightened of the possibility getting cancer or memory loss), the intention to choose fortified or functional food increased (Cox & Bastiaans, ; Cox, Koster, & Russell, ; Henson, Cranfield, & Herath, ). Perceived behavioral control: This factor is part of the Theory of Planned Behavior (Ajzen, ) and comprises components that reflect beliefs about controllability and about self‐efficacy (Ajzen, ). The latter also belongs to the Protection Motivation Theory by Rogers () and refers to the individual's belief that they can cope with the health threat by a recommended behavior, for example, buying a new food product.…”
Section: Results Of the Reviewmentioning
confidence: 99%
“…In line with previous investigations on the construct perceived behavioral control (Ajzen, ; Povey, Conner, Sparks, James, & Shepherd, ), self‐efficacy was more often significantly influencing consumers’ new food technology evaluation than controllability. A positive influence of self‐efficacy on consumers’ evaluation of new food technologies was demonstrated with respect to GM (Cox, Evans, & Lease, ), biofortification (De Steur, Mogendi, Wesana, Makokha, & Gellynck, ; Mogendi et al., ), and fortification (Cox et al., ; Henson et al., ; Henson et al., ; Tudoran, Scholderer, & Brunso, ). This was also highlighted in the context of Australian consumers’ intentions to consume conventional and novel sources of long‐chain mega‐3 fatty acids (for example, GM food), where self‐efficacy (confidence to consume) was the most important predictor (Cox et al., ).…”
Section: Results Of the Reviewmentioning
confidence: 99%